Loss of the putative Rab GTPase, Ypt7, impairs the virulence of Cryptococcus neoformans - Hu, Guanggan; Qu, Xianya; Bhalla, Kabir; Xue, Peng; Bakkeren, Erik; Lee, Christopher W. J.; Kronstad, James W. (Frontiers in Microbiology, 2024)
Small GTPases of the Rab family coordinate multiple membrane fusion and trafficking events in eukaryotes. In fungi, the Rab GTPase, Ypt7, plays a critical role in late endosomal trafficking, and is required for homotypic fusion events in vacuole biogenesis and inheritance. In this study, we identified a putative YPT7 homologue in Cryptococcus neoformans, a fungal pathogen causing life threatening meningoencephalitis in immunocompromised individuals. As part of an ongoing effort to understand mechanisms of iron acquisition in C. neoformans, we established a role for Ypt7 in growth on heme as the sole iron source. Deletion of YPT7 also caused abnormal vacuolar morphology, defective endocytic trafficking and autophagy, and mislocalization of Aph1, a secreted vacuolar acid phosphatase. Ypt7 localized to the vacuolar membrane and membrane contact sites between the vacuole and mitochondria (vCLAMPs), and loss of the protein impaired growth on inhibitors of the electron transport chain. Additionally, Ypt7 was required for robust growth at 39 o C, a phenotype likely involving the calcineurin signaling pathway because ypt7 mutants displayed increased susceptibility to the calcineurin-specific inhibitors, FK506 and cyclosporin A; the mutants also had impaired growth in either limiting or high levels of calcium. Finally, Ypt7 was required for survival during interactions with macrophages, and ypt7 mutants were attenuated for virulence in a mouse inhalation model thus demonstrating the importance of membrane trafficking functions in cryptococcosis.